Selected anthropometric characteristics as the predictors of performance in boxing - Kumar, D.; Tyagi. S. (Journal of Management Research and Analysis, 2019)
The study aimed to assess the selected anthropometric characteristics as the predictors of performance in boxing. Seventy (N=70) male boxing players were selected as the subject ofthe study. The age of the subjects ranged between 17 to 25 years. Out of seventy, forty one (N=41) were state level boxing players and twenty nine (N=29) were having participation in the Nationals and International games. The height range was 152 cm to 192 cm and weight was 45 kg to 98 kg, body fat % 9.22 to 31.55, arm length 70 cm to 90 cm, forearm length 42 cm to 58 cm, leg length 90 cm to 116 cm.Selected anthropometric components were selected for the study. Descriptive statistics (mean and standard deviation) and multiple regression step wise was applied for data analysis and theperformance of the boxing players was assessed by scoresheet provided by the three panel of judges of Sports Authority of India. Differences were considered significant at 0.05 level.